The automatic experimental design for modeling the reaction mechanisms of chemical vapor deposition processes. Issue 7 (7th May 2015) - Takahashi, Takahiro; Ema, Yoshinori; Hoffmann, Patrik; Knez, Mato; Vahlas, Constantin; Alexandrov, Sergei
Abstract The identification of an appropriate reaction model (reaction mechanism) that indicates the reaction paths from source gases to films is one of the most important facets for developing chemical vapor deposition (CVD) processes. Previously, we developed a system that automatically identifies the kinetic models of reaction mechanisms involved in experimental results by the CVD processes using genetic algorithms (GAs). However, in order to automate the entire process of CVD development, it is necessary to automate the other processes associated with the reaction‐modeling process. Therefore, in this study, we proposed the method to automate the experimental design to determine more appropriate the reaction models. In addition, we developed the automatic system to design the experiments for the models. We demonstrated the feasibility and validity of the method using a simplified and synthetic CVD process. The system automatically and appropriately designed the experiments from the information of the reaction model candidates without using the knowledge of reaction engineering directly. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)